Handbook of Japanese popular culture (Greenwood Press, 1989)
The Handbook of Japanese Popular Culture provides a convenient and efficient guide to the prevalent ways of life, recreations, and artistic creations of contemporary Japan. Designed for the general reader as well as the specialist in Japanese culture. The areas explored are those that have proven to be of durable interest to the Japanese, such as sports, science fiction, and popular music, as well as passing fads and fancies. The extremely readable essays, contributed by specialists in the field, provide a wealth of interesting information, including a survey of the historical development of the topic under discussion, with special attention paid to the most useful published works in the field, followed by a guide to the research collections and reference works that should be consulted by those wishing to deepen their knowledge of the subject. Exploring the most salient aspects of Japanese popular culture, the chapters include such topics as popular architecture, new religions, popular performing arts, film, television, comics, and mystery literature. The editor's introduction suggests that the study of popular culture as a discipline with its own unique subject matter and methodology represents a form of protest against the concept of culture as a selective tradition consisting of the best that has been thought and said. This comprehensive survey of Japanese popular culture will be an essential additon to all libraries and a useful resource in the study of popular culture, sociology, Japanese history and culture, humanities, communications, and journalism.